Dampak Pengembangan Alun-Alun Kota terhadap Kondisi Sosial dan Ekonomi Masyarakat Sekitarnya: Studi Kasus Kawasan Pinggiran Kota Curug, Indonesia - Anna Karenina; Irma Dwi Andini; Forina Lestari (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2026)
This study examines socio-economic and spatial transformations resulting from the development of Curug Town Square in Tangerang Regency, Indonesia. Previously characterized by informal settlements, fragmented circulation, and small-scale household enterprises, the area experienced significant change following the establishment of the square as a multifunctional public space. A qualitative descriptive approach was employed through field observations, interviews, and document analysis to understand community adaptation to new spatial and economic conditions. The findings indicate that the town square revitalized local commercial activities, encouraged micro-entrepreneurship, and strengthened social interaction by functioning as a center for cultural and daily community activities. Spatially, redevelopment improved accessibility, safety, and urban identity by introducing more organized spatial arrangements. However, the transformation also generated uneven impacts, including displacement pressures on long-term traders, rising land values indicating early gentrification, and shifts in traditional social dynamics. The study highlights the importance of inclusive planning to ensure equitable urban transformation in semi-urban contexts.